PERSEPSI GURU DAN SISWA TERHADAP MEDIA WORDWALL SEBAGAI APLIKASI PEMBELAJARAN IPA KELAS VIII DI SMP NEGERI 26 MAKASSAR. - Mistahul jannah; Nawir; Akram (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore the perceptions and experiences of teachers andstudents regarding the use of Wordwall as an evaluation medium in eighth-gradescience learning at SMP Negeri 26 Makassar. This study started from the problemof the need to increase student engagement and the effectiveness of feedback intraditional evaluation methods. Conducted for one month starting on March 14,2025, this study used a qualitative approach. Data collection was conductedthrough direct observation of the use of Wordwall in class, in-depth interviews withone science teacher and eight eighth-grade students from different backgrounds,and documentation analysis. Data were analyzed systematically through thestages of data reduction, data presentation, and conclusion drawing. Data validitywas maintained through source triangulation techniques, member checks (dataconfirmation with participants), and audit trails. The results showed that the use ofWordwall as an evaluation medium in the science learning process had a positiveimpact, especially increasing student interactivity and motivation. Both teachersand the majority of students considered this media able to make the evaluationprocess more interesting, interactive, and fun thanks to gamification features suchas quizzes and interactive puzzles, as well as fast automatic feedback. Thissignificantly helped students in understanding science material. However, thisstudy also identified technical challenges in the form of unstable internetconnections and limited devices, which were major barriers to implementation.Students perceptions of the use of Wordwall varied; most reported increasedmotivation and enthusiasm, while others felt the effect was neutral. Somesuggestions for improvement included adding a variety of questions, providingexplanations after completing the questions, and enhancing the interface to makeit more interactive.